Mobility and freedom of movement: A novel out-of-hospital treatment for pediatric patients with terminal cardiac insufficiency and a ventricular assist device - Rottermann, Kathrin; Dittrich, Sven; Dewald, Oliver; Teske, Andreas; Kwapil, Nicola; Bleck, Steffen; Purbojo, Ariawan; Münch, Frank (Frontiers in Cardiovascular Medicine, 2022)
Background: Due to rapid medical and technological progress, more and more pediatric patients with terminal cardiac insufficiency are being implanted with a ventricular assist device as a bridge to transplant without legal approval for hospital discharge. EXCOR (R) Active is a recently developed mobile driving unit for the EXCOR (R) ventricular assist device (EXCOR (R) VAD) with a long-lasting battery life that can manage small blood pumps, offering improved mobility for pediatric patients. This study strives to elaborate the requirements necessary for a safe home healthcare environment (HHE) for pediatric patients on EXCOR (R) VAD powered by the EXCOR (R) Active driving unit. Materials and methods: Patient- and device-related preconditions (medical, ethical, psychological, technical, structural, organizational) were analyzed with regard to feasibility and safety in three individual patient cases. Included were pediatric patients with terminal cardiac insufficiency in a stable medical condition receiving in-hospital treatment with a univentricular or biventricular EXCOR (R) VAD powered by EXCOR (R) Active. Analysis was single-center, data was obtained 05/2020-02/2022. Results: A total of three patients on EXCOR (R) VAD were identified for HHE treatment with the EXCOR (R) Active driving unit. Switch was performed safely and increased mobility led to improved psychomotor development and improved quality of life. No complications directly related to HHE-treatment occurred. One patient recently underwent an orthotopic heart transplant, one patient remains in HHE, and one patient died due to a complication not related to the HHE. Ethical approval for off-label use was obtained and patients and parents were given the required technical training and psychological support. Caregivers and medical professionals involved in the patients' care at home were briefed intensely. Remote consultations were implemented and interdisciplinary in-hospital checks reduced to a long-term 4-week-scheme. Conclusion: While it is challenging to discharge pediatric patients being treated with a paracorporeal ventricular assist device (EXCOR (R) VAD) from hospital, it is feasible and can be managed safely with the novel driving unit EXCOR (R) Active. A HHE may help to improve patients' psychomotor development, offer normalized social contacts and strengthen both patients' and parents' physical and mental resources. Legal approval and another study with a larger sample size are warranted.
CRIS-Team WoS Importer:2022-12-30